2012
DOI: 10.1080/03601234.2012.638886
|View full text |Cite
|
Sign up to set email alerts
|

Biological degradation and microbial function effect of norfloxacin in a soil under different conditions

Abstract: This paper investigated the degradation kinetics of norfloxacin in a soil, and its effects on soil respiration and nitrogen transformation under different conditions. Compared to the sterile control, the degradation rates of norfloxacin in the non-sterile soil were greatly enhanced, suggesting that microorganisms played a major role in the degradation. Accelerated degradation for norfloxacin in the soil was observed with decreasing concentrations (30 mg/kg to 5 mg/kg) with its half-life decreasing from 62 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…A study by Wang et al (2006) revealed that the half-life of sulfadimethoxine in soil decreased from 10.4 days to 6.9, and again to 4.9 days when the soil moisture content was increased from 15, to 20, and 25%, respectively. A similar effect of temperature was shown in the case of the degradation of norfloxacin (Yang et al, 2012).…”
Section: Fate Of Antibiotics In Soilsupporting
confidence: 73%
“…A study by Wang et al (2006) revealed that the half-life of sulfadimethoxine in soil decreased from 10.4 days to 6.9, and again to 4.9 days when the soil moisture content was increased from 15, to 20, and 25%, respectively. A similar effect of temperature was shown in the case of the degradation of norfloxacin (Yang et al, 2012).…”
Section: Fate Of Antibiotics In Soilsupporting
confidence: 73%
“…Stimulation was also observed in soil microcosms treated with CIP [92] and NOR [74]. In these experiments, nitrification was stimulated only at the lowest doses tested (1 mg· kg…”
Section: Effects Of Antibiotics On Nitrificationmentioning
confidence: 76%
“…The relatively short-term persistence of VA in soil might also be related to its solubility in water and its low affinity to adsorption by various components of the soil (Thiele-Bruhn, 2003 ). Antibiotics are subjected to various processes in the soil such as volatilization, transformation or degradation, sorption-desorption, uptake by plants and transport into groundwater and surface waters (Accinelli et al, 2007 ; Lin and Gan, 2011 ; Yang et al, 2012 ; Manzetti and Ghisi, 2014 ; Awad et al, 2016 ; Pan and Chu, 2016 ; Topp et al, 2016 ). However, many factors such as the chemical structure, properties and concentration of an antibiotic, the physico-chemical properties of the soil, the microbial population and the incubation conditions play a major role in the degradation of antibiotics in soil.…”
Section: Discussionmentioning
confidence: 99%